Enzymatic Hydrolysis of Marine Collagen and Fibrinogen Proteins in the Presence of Thrombin - Ludmila L. Semenycheva; Marfa N. Egorikhina; Victoria O. Chasova; Natalya B. Valetova; Yulia L. Kuznetsova; Alexander V. Mitin (Marine Drugs, 2020)
Enzymatic hydrolysis of native collagen and fibrinogen was carried out under comparable conditions at room temperature. The molecular weight parameters of proteins before and after hydrolysis by thrombin were monitored by gel-penetrating chromatography (GPC). An analysis of the experiment results shows that the molecular weight parameters of the initial fibrinogen (Fn) and cod collagen (CC) are very similar. High molecular CC decays within the first minute, forming two low molecular fractions. The main part (~80%) falls on the fraction with a value of Mw less than 10 kDa. The initial high molecular fraction of Fn with Mw ~320–340 kDa is not completely hydrolyzed even after three days of control. The presence of low molecular fractions with Mw ~17 and Mw ~10 kDa in the solution slightly increases within an hour and noticeably increases for three days. The destruction of macromolecules of high molecular collagen to hydrolysis products appears almost completely within the first minute mainly to the polymer with Mw ~10 kDa, and enzymatic hydrolysis of fibrinogen proceeds slower than that of collagen, but also mainly to the polymer with Mw ~10 kDa. Comparative photos of the surfaces of native collagen, fibrinogen and the scaffold based on them were obtained.